2017
DOI: 10.3390/su9050688
|View full text |Cite
|
Sign up to set email alerts
|

Green Supplier Evaluation and Selection Using Cloud Model Theory and the QUALIFLEX Method

Abstract: Nowadays, companies have to improve their practices in the management of green supply chain with increased awareness of environmental issues worldwide. Selecting the optimum green supplier is crucial for green supply chain management, which is a challenging multi-criteria decision making (MCDM) problem. Moreover, while evaluating the performance of alternative suppliers, decision makers tend to determine their assessments using linguistic descriptors due to experts' vague knowledge and information deficiency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 58 publications
0
63
0
Order By: Relevance
“…Qin et al [11] introduced the TODIM method into an interval type-2 fuzzy set and presented an MCGDM approach to handle green supplier selection. To evaluate the green performance of suppliers, Wang et al [3] developed a comprehensive approach according to the cloud model and QUALIFLEX (QUALitative FLEXible multiple criteria) method. Yazdani et al [43] presented a synthetical approach for green supplier selection by combining the decision-making trial and evaluation laboratory method, quality function deployment model, and complex proportional assessment.…”
Section: Methods For Green Supplier Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qin et al [11] introduced the TODIM method into an interval type-2 fuzzy set and presented an MCGDM approach to handle green supplier selection. To evaluate the green performance of suppliers, Wang et al [3] developed a comprehensive approach according to the cloud model and QUALIFLEX (QUALitative FLEXible multiple criteria) method. Yazdani et al [43] presented a synthetical approach for green supplier selection by combining the decision-making trial and evaluation laboratory method, quality function deployment model, and complex proportional assessment.…”
Section: Methods For Green Supplier Selectionmentioning
confidence: 99%
“…GSCM includes various activities, such as green product development, green purchasing, green production, green packaging, green warehousing, green marketing, green transportation, resource recycling, and green supplier selection. In these activities, green supplier selection can directly influence the competitiveness of a supply chain and the environmental performance of an enterprise [3], and it is a key part of GSCM [4]. Furthermore, efficient supply chain management can help enterprises to minimize supply chain and production risk, optimize inventory management, improve customer service levels, enhance competitive advantage, and increase profitability and customer satisfaction [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Ulutas et al [46] reported a utility-driven framework for supplier evaluation and selection, which combines fuzzy AHP, fuzzy complex proportional assessment, and fuzzy linear programming, and validated it through an application in a Turkish textile company. Wang et al [47] reported an integrated MCDM method based on cloud model theory and the qualitative flexible multiple criteria method (QUALIFLEX) to assess the green performance of companies under economic and environmental criteria. Yazdani et al [48] put forward an integrated framework for green supplier selection by combining the decision-making trial and evaluation laboratory (DEMATEL) method, the quality function deployment (QFD) model, and the complex proportional assessment (COPRAS) Symmetry 2017, 9, 169 4 of 16 approach, and Yazdani et al [49] delivered an integrated green supplier selection model using step-wise weight assessment ratio analysis (SWARA), QFD, and WASPAS methods.…”
Section: Hybrid Methodsmentioning
confidence: 99%
“…The principle of QUALIFLEX method is to test all the possible permutations of candidates and determine the optimal one that displays the maximum comprehensive concordance/discordance index . Comparing with other MCDM approaches, the core merits of the QUALIFLEX approach are that (a) it can cope with the cardinal and ordinal information correctly; (b) it can effectively solve the complicated MCDM problems with numerous criteria and limited alternatives; (c) its calculation process is easy, and the result can be obtained efficiently. Therefore, it is desirable to apply the QUALIFLEX method to deal with robot selection problems.…”
Section: Introductionmentioning
confidence: 99%